Separation of the pyro- and piezoelectric response of electroactive polymers for sensor applications - Castro, H. F. (2006)
One of the main problems for the use of ferroelectric materials for sensor applications, especially for tactile sensors, is the separation of the pyro- and piezoelectric responseproduced by temperature and pressure changes, respectively. We present two different approaches to achieve this goal. The first approach is based on the study of the signal in the frequency domain and uses a signal processing to separate the piezoelectric response from the pyroelectric one. The second approach is based on a double layer configuration of electroactive polymers. In this case, the piezoelectric response is equal in each layer, whereas, the pyroelectric response dominates in the layer exposed to the temperature variations. The pyro- and piezoelectric responses are separated by estimating the difference between the signals of two layers and the signal from one of the layers, correspondingly.